Out in the center : public controversies and private struggles - Denny, Harry C.; Mundy, Robert; Naydan, Liliana M.; Sévère, Richard; Sicari, Anna (Utah State University Press, 2018)
"Explores the personal struggles of tutors, administrators, and directors in the public space of the writing center, analyzing how the writing center community can better enable staff to negotiate moments of controversy by studying the intersection of public moments with private conflicts of identity"--Provided by publisher